Press-ekspress . Press-ekspress . Press Express . Пресс-экспресс - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Program discussing the Russian Federation Constitutional Court's decision regarding the "Izvestia" newspaper's complaint on the constitutionality of the 17 July 1992 Supreme Council of the Russian Federation decree. The program also reviews press opinions on new drafts of the Constitution. Featured in the program: Golembiovskii, Igor' Nestorovich (Chief Editor of the Newspaper "Izvestia"); Riurikova, Natal'ia (Chief Editor of the Anthology "Kinostsenarii" [Screenplays]) Contributors: Egorshev, Andrei (Anchor) Series description: Press reviews, interviews with journalists, presentations of magazines and newspapers. Обсуждение решения Конституционного Суда Российской Федерации по жалобе членов журналистского коллектива редакции газеты "Известия", в которой оспаривалась конституционность постановления Верховного Совета Российской Федерации от 17 июля 1992 г. "О газете "Известия"; обсуждение в прессе новых проектов Конституции Российской Федерации. В программе участвуют: Голембиовский, Игорь Несторович (Главный редактор газеты «Известия»); Рюрикова, Наталья (Главный редактор альманаха "Киносценарии") Создатели: Егоршев, Андрей (Ведущий/Ведущая) Описание серии: Обзор прессы, интервью с журналистами, представление журналов и газет.